2017
DOI: 10.1111/acem.13172
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as an Adjunct to Opioids for Acute Pain in the Emergency Department: A Randomized Controlled Trial

Abstract: Ketamine, as an adjunct to opioid therapy, was more effective at reducing pain over 120 minutes and resulted in a lower total opioid dose as well as fewer repeat doses of analgesia. More side effects were reported in the ketamine group (51% vs. 19%), but the side effect profile appears tolerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 21 publications
0
30
0
5
Order By: Relevance
“…Recently, administrations of low, sub-anesthetic doses of ketamine either alone or as an adjunct to opioid therapies have been shown to be an effective treatment in postoperative and acute pain settings [ 8 12 ]. In addition, ketamine has long been safely used as an general anesthetic and analgesic agent [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, administrations of low, sub-anesthetic doses of ketamine either alone or as an adjunct to opioid therapies have been shown to be an effective treatment in postoperative and acute pain settings [ 8 12 ]. In addition, ketamine has long been safely used as an general anesthetic and analgesic agent [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose boluses of ketamine (0.1-0.3 mg/kg) have been shown to reduce pain scores and opiate consumption when used as an adjunct to opiate therapy in acute pain treatment. 9,14,15 Clinical benefits can last up to 2 hours Continuous infusions can reduce consumption of opiates and concomitant sedatives.…”
Section: Bolus Dosingmentioning
confidence: 99%
“…after a single administration. 15 Compared with lower doses, a dose of 0.3 mg/kg has been found to be more effective in reducing pain scores. 9 However, higher doses are associated with more frequent minor adverse events.…”
Section: Bolus Dosingmentioning
confidence: 99%
“…A double-blind randomized placebo trial found that ketamine, as an adjunct, was effective in acute pain control and lowered the overall opioid dose utilized by the patients in the ketamine group [29]. Although further studies are needed to further evaluate the efficacy of ketamine versus other opioid analgesics with higher confidence, it is important to recognize the lower demand and lower dose administration of opioid analgesics while using ketamine for acute pain control [29].…”
Section: Comparison In the Reduction Of Acute Painmentioning
confidence: 99%